A visco-hyperelastic constitutive model and its application in bovine tongue tissue. (11th April 2018) - Yousefi, Ali-Akbar Karkhaneh; Nazari, Mohammad Ali; Perrier, Pascal; Panahi, Masoud Shariat; Payan, Yohan
Abstract: Material properties of the human tongue tissue have a significant role in understanding its function in speech, respiration, suckling, and swallowing. Tongue as a combination of various muscles is surrounded by the mucous membrane and is a complicated architecture to study. As a first step before the quantitative mechanical characterization of human tongue tissues, the passive biomechanical properties in the superior longitudinal muscle (SLM) and the mucous tissues of a bovine tongue have been measured. Since the rate of loading has a sizeable contribution to the resultant stress of soft tissues, the rate dependent behavior of tongue tissues has been investigated via uniaxial tension tests (UTTs). A method to determine the mechanical properties of transversely isotropic tissues using UTTs and inverse finite element (FE) method has been proposed. Assuming the strain energy as a general nonlinear relationship with respect to the stretch and the rate of stretch, two visco-hyperelastic constitutive laws (CLs) have been proposed for isotropic and transversely isotropic soft tissues to model their stress-stretch behavior. Both of them have been implemented in ABAQUS explicit through coding a user-defined material subroutine called VUMAT and the experimental stress-stretch points have been well tracked by the results of FE analyses. It has been demonstrated that the proposed laws make a good description of the viscous nature of tongue tissues. Reliability of the proposed models has been compared with similar nonlinear visco-hyperelastic CLs.